Relationship between Alcohol Consumption and Impaired Liver Function - Agustina W. Djuma; Novian A. Yudhaswara; Suzanne Patricia Dardeau (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2020)
East Nusa Tenggara is a province of high alcohol abuse in Indonesia. Ngada Regency has a prevalence of 38.8%. The high prevalence is inseparable from traditional factors and socio-cultural norms which strongly influence the habit of consuming alcohol, the cold temperature in this area further strengthens this habit. The impact of alcohol consumption is the emergence of various types of diseases, one of which is impaired liver function such as alcoholic liver disease. The objective of this study is to determine the relationship between alcohol consumption and impaired liver function in communities in Bajawa and Golewa Districts, Ngada Regency. This research method is an observational analytic with cross-sectional design. The research subjects were 55 people who consumed alcohol in Golewa and Bajawa Districts, who had met the inclusion criteria. Alcohol consumption was measured by the AUDIT (The Alcohol Use Disorders Identification Test) questionnaire, while the parameter for liver disorders was the level of Gamma Glutamyl Transferase (GGT). The prevalence of liver dysfunction based on GGT examination was 15%. Meanwhile, the relationship between alcohol consumption and impaired liver function was tested with the Spearman correlation with α 0.05, the correlation value was p = 0.413, which means it has a moderate or significant, not too strong relationship. It is recommended that the people of Ngada Regency reduce alcohol consumption so that it can reduce the risk of impaired liver function.